Health effects of Hevea brasiliensis wood dust exposure among furniture factory workers - Yusof, Muhammad Zubir; Hod, Rozita; Noor Aizuddin, Azimatun; Samsuddin, Niza (Light House Polyclinic (Índia), 2019)
Abstract: Background: Potential health impacts resulting from wood dust exposure among workers in the furniture factories have been reported in many studies. However, most of the studies focused on pine, beech, teak, oak and red western cedar. Studies on the health effects due to rubber wood (Hevea brasiliensis) dust are still lacking, thus there is a need to explore this public health issue further. This study assessed the respiratory and skin health effects among workers exposed to rubber wood dust in the furniture factory. Method: A crosssectional study was conducted among 241 workers in a furniture factory located in Peninsular Malaysia. The data was collected through face-to-face interview by using questionnaire and spirometry. Result: The level measured in the material supply and machinery area showed the concentration level of rubber wood dust exceeded the permissible exposure limit of 1 mg/m3. Workers exposed to rubber wood dust showed the highest prevalence of eye symptoms (n=125, 51.9%) and nasal symptoms (n=122, 50.6%). High exposed group was more likely to complain on eye symptoms (adjusted OR=3.89, 95% CI=2.03 to 7.49) and nasal symptoms (adjusted OR=2.63, 95% CI=1.41-4.91). Workers worked for ten years or greater were higher risk to have phlegm (adjusted OR=4.59, 95% CI=1.25 to 16.86) chest tightness (adjusted OR=6.33, 95% CI=2.16 to 18.53), breathlessness (adjusted OR=9.84, 95% CI=2.75 to 35.26), and eyes symptoms (adjusted OR=3.67, 95% CI=1.24 to 10.89). The high exposed group and workers who worked for ten years or greater showed decreased lung function, but only high exposed group showed statistically significant findings. Conclusion: Appropriate preventive and control measures should be implemented to protect workers in the rubber wood furniture factory.